2019
DOI: 10.1097/icl.0000000000000517
|View full text |Cite
|
Sign up to set email alerts
|

Polymicrobial Keratitis With Cryptococcus curvatus, Candida parapsilosis, and Stenotrophomonas maltophilia After Penetrating Keratoplasty: A Rare Case Report With Literature Review

Abstract: Cryptococcus curvatus should be added to the known list of organisms capable of causing fungal keratitis. Our experience suggests that this type of organism could cause low-grade, grumbling infection, which may however be exceptionally difficult to treat. Long-term eradication of this rare fungal keratitis could be potentially achieved by intensive ocular and systemic antifungal treatment, repeat therapeutic keratoplasties, and focal cryotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…Moreover, it is well established that C. neoformans is responsible for the majority of cryptococcal infections, while C. deneoformans is less common [ 8 ]. Among Cryptococcus species outside of the C. neoformans / C. gattii species complex, the following species have been described as causing occasional infections in humans: C. laurentii [ 10 13 ], C. albidus [ 10 , 14 16 ], C. curvatus [ 17 , 18 ], C. uniguttulatus [ 19 ], and C. adeliensis [ 20 ]. Such casuistic infections, reviewed in literature most recently by Smith et al [ 21 ] can be also systemic in case of strains able to grow at 37°C.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is well established that C. neoformans is responsible for the majority of cryptococcal infections, while C. deneoformans is less common [ 8 ]. Among Cryptococcus species outside of the C. neoformans / C. gattii species complex, the following species have been described as causing occasional infections in humans: C. laurentii [ 10 13 ], C. albidus [ 10 , 14 16 ], C. curvatus [ 17 , 18 ], C. uniguttulatus [ 19 ], and C. adeliensis [ 20 ]. Such casuistic infections, reviewed in literature most recently by Smith et al [ 21 ] can be also systemic in case of strains able to grow at 37°C.…”
Section: Introductionmentioning
confidence: 99%
“…laurentii (Castro-Lainez et al, 2019), C. albidus (Choe et al, 2019), C. curvatus (Ting et al, 2019), C. uniguttulatus (McCurdy and Morrow, 2003), and C. adeliensis (Rimek et al, 2004), have been reported occasionally and generally in immunocompromised hosts.…”
Section: Cryptococcosismentioning
confidence: 99%
“…will be used to refer to all these species to make it more understandable. The oldest data correspond to cases of F. uniguttulatum (1934), H. luteolus (1956), and F. magnus (1960) infections [10][11][12], while the most recent data correspond to reports of F. magnus (2018), C. curvatus (2018), and C. cyanovorans (2018) [3,13,14].…”
Section: Rare Cryptococcus Spp As Agents Of Human Mycosesmentioning
confidence: 99%
“…After analyzing the published data, it is clear that molecular identification is mandatory to reach an unequivocal taxonomical classification of these rare Cryptococcus species. Sequencing of the internal transcribed spacer (ITS1 and ITS2) together with D1/D2 regions of the rDNA were the methods of choice for molecular identification [1,13,15,20,22,28] (Table 1). Despite this fact, only 43.4% of the strains (25 out 58) included in this review were identified by molecular methods.…”
Section: Direct Examination Indian Ink and Serologymentioning
confidence: 99%